Serum polychlorinated biphenyls and bisphenol-A levels in Nigerian women with breast cancer (2014)
Endocrine disruptors (EDs)-polychlorinated biphenyls (PCBs) and bisphenol-A (BPA) have been associated with increased risk of breast cancer (B.Ca). In Nigeria, there is increase in breast cancer incidence. This has been attributed to increased use and exposure to EDs. Although, several studies have been done on breast cancer, there is paucity of information on the serum levels of these EDs in Nigerian women. This study therefore aims at determining the serum levels of PCBs and BPA in breast cancer patients.Eighty women aged 18-70 years were recruited with informed consent after institutional ethical approval. They were 40 participants with breast cancer pre-treatment (cases) matched with 40 apparently healthy women (controls). They were recruited from a tertiary hospital in Ibadan, Nigeria. Demographic indices: age, age at menarche (AM), age at menopause (AMP) and anthropometric indices: height, weight, body mass index (BMI), waist circumference (WC), hip circumference (HC), waist-hip ratio (WHR) and waist-height ratio (WHT) were obtained from the pre-test questionnaire administered and standard methods respectively.10 ml of venous blood was collected from each participant and sera obtained were analyzed for PCB and BPA. These were determined by High performance liquid chromatography (HPLC). Data were analyzed using Student t-test and Pearson correlation coefficient, p was significant at <0.05.Results showed increases in the height, weight, WC, HC, WHR, WHT, PCB and BPA serum levels in cases compared with controls. Positive correlations were observed among WC and WHR, WHT, HC; HC and WHT; WHR and WHT in both cases and controls. However, positive correlations among height, weight, WC and WHR; BMI and weight were observed in cases only. Weight correlated negatively with age at menarche (AM) only in controls. The differences and correlations were statistically significant (p<0.05).Mechanisms involving PCB, BPA and adiposity may be involved in breast cancer aetiology. Reduction of environmental pollution and dietary modulation may be helpful.